Komodifikasi Bonek dalam Jejaring Konglomerasi Jawa Pos - Fajar Junaedi; Heru Nugroho; Sugeng Bayu Wahyono (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2018)
Persebaya is one of the biggest and most successful football clubs in Indonesian football history. This football club has very loyal fans who called Bonek. This study aims to find the implications of the ownership of Persebaya by Jawa Pos by analyzing the commodification of Jawa Pos against Bonek, the Persebaya fans. This study deploys political economy of media theory, especially commodification theory. Using qualitative method, this research focuses on case studies of researc h subjects namely Jawa Pos and Bonek. The result shows the commodification relation between Jawa Pos and Bonek Persebaya. At the beginning, the growing relationship between Jawa Pos and Persebaya was the relationship between the media and the football club, but the relationship changed when Jawa Pos took over the shares of Persebaya in 2017. By taking over the shares of Persebaya, Jawa Pos becomes the legal owner of Persebaya. Since becoming an owner, Jawa Pos is more than just covering Persebaya. Jawa Pos practices commodification in the newsroom in the form of the production of various products about Persebaya and Bonek—Persebaya fans.